Tuberculosis of knee joint and tubercular pyomyositis of gastrocnemius muscle. - Ahmed, S; Shahin, MA; Kader, MA; Banik, J; Azad, AK; Haq, SA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):724-7 The abstract of this article is available on the PubMed website